Compound Sentences Study and Abnormalities in Their Construction: Theoretical Aspects (Linguostylistic Studies, 2018)
An important place in the construction of oral and written statements is occupied by the compound sentences – one of the oldest structural-semantic language formations in the complex sentence system. The role of conjunctions in this type of sentences is important both in speech and in writing. They provide the cohesion between the parts of the text and allow us to construct long sentences.The article analyzes the general theoretical issues related to the aspects of studying, the delimitation of structural-semantic types compound sentences in constructions with the semantic conjunctions, which, depending on the context, can express different meanings or combine several meanings ​​simultaneously. The estension of the subordinating conjunctions range, the delimitation of compound sentences and simple sentences with homogeneous parts of the sentences (predicates) are of particular interest for this study. The study highlights the issues of the delimitation of compound, complex and asyndetic clauses, specific approaches to the definitions in parataxis.The practical importance of the study of compound sentences is obvious owing to the exact, relevant and the convincing for each particular situation of communication definition of the functions of the syntactical units under consideration. The most common mistakes revealed in the oral and written speech of the Ukrainian language native speakers are systematized. First of all, it concerns the peculiarities of the syntactical structures components and these components arrangement, logical connections between the components, an appropriate use of the punctuation marks, the connective elements and their usage, coordination of the verb- predicates forms, stylistic appropriateness, etc. The edited versions of the sentence units are suggested.In the course of the study we came to the conclusion that today linguists are not unanimous about the status of compound sentences, their structural-semantic types and the means of connecting the structure components. Far from being an exhaustive analysis of the syntactic abnormalities has shown a high degree of their predominance in the compound sentence. We advocate further research on the linguistic-stylistic aspect of the compound sentences, analysis of the detected abnormalities in terms of their perception by the recipients and determination of the degree of «abnormality».
Keywords: compound sentence; definition; coordinative conjunction; structural-semantic type; linguistic norm; linguistic error (abnormality)